Comparative analysis of the imported segment of the chemical–pharmaceutical veterinary medicinal products market in Ukraine and Poland: market structure, international manufacturers and product portfolios - O. V. Hodovskyi; O. M. Azaman; S. O. Boianovskyi; V. V. Chumachenko; O. V. Tashuta (One Health Journal, 2026)
Ukraine's progress towards European Union integration has created a need for a comprehensive evaluation of the national veterinary medicinal products (VMPs) market and its comparison with those of EU Member States. This study aimed to compare the imported segment of the chemical–pharmaceutical veterinary medicinal products market in Ukraine and the Republic of Poland by analysing its geographical structure, the composition of international manufacturers, and the breadth of their product portfolios. The study was based on the official State Registers of VMPs in Ukraine and the Republic of Poland (March, 2026). Only imported chemical–pharmaceutical veterinary medicinal products (CP-VMPs) were included in the analysis. Bibliographic and content analysis, together with classification, systematisation, structural and comparative analyses, descriptive statistics, and graphical methods, were applied. In addition, a set of structural indicators was developed to evaluate geographical diversification, manufacturer density, and portfolio depth within the imported market segment. Imported CP-VMPs accounted for 487 of 1,186 registered products (41.1 %) in Ukraine and 1,587 of 1,795 (88.4 %) in Poland. The Ukrainian imported segment comprised products from 122 manufacturers representing 39 exporting countries, whereas the Polish market included products from 180 manufacturers representing 22 countries. The average number of manufacturers per exporting country was 3.13 in Ukraine and 8.18 in Poland, while the average number of products per manufacturer reached 4.0 and 8.82, respectively. The corresponding average numbers of products per exporting country were 12.49 and 72.14. These findings demonstrate two distinct models of market organisation. Ukraine is characterised by broad geographical diversification combined with relatively shallow manufacturer portfolios, whereas the Polish market demonstrates a substantially higher concentration of international manufacturers and considerably deeper product portfolios despite a smaller number of exporting countries. Although both markets share a largely common group of leading international manufacturers, the ten largest companies market considerably broader product portfolios in Poland (49 – 138 registered products) than in Ukraine (15–46 registered products). The study proposes a novel set of structural indicators for evaluating imported veterinary pharmaceutical markets by distinguishing geographical diversification, portfolio saturation, and manufacturer presence. The findings indicate that the principal difference between the Ukrainian and Polish markets lies not in the composition of international manufacturers but in the depth and completeness of their product portfolios.